Cardiovascular risk factors and Parkinson’s disease in 500,000 Chinese adults - Clarke, R; Lewington, S; Mappin‐Kasirer, B; Turnbull, I; Guo, Y; Bian, Z; Chen, Y; Yang, L; Chen, Z; Clarke, R; China Kadoorie Biobank (Wiley, 2019)
Objective The objectives of this study were to compare the risks of Parkinson's disease among those with versus those without prior stroke or heart disease at baseline in a prospective study of 0.5 million adults in China, and to examine associations of cardiovascular disease risk factors (cigarette smoking, hypertension, diabetes, obesity) with risk of Parkinson's disease. Methods During an average of 11.5 years of follow‐up of 503,497 middle‐aged participants in the China Kadoorie Biobank study, 603 incident cases were hospitalized with a diagnosis of Parkinson's disease. Cox proportional hazards models were used to assess associations of history of heart disease or stroke with Parkinson's disease in all participants, and of cardiovascular disease risk factors with Parkinson's disease in a subset without prior cardiovascular disease. Results In this population the incidence rate of Parkinson's disease (mean [SD] age of cases, 61 [10] years) was 13.3 (95% confidence interval: 12.3–14.4) per 100,000 person‐years. Incidence increased with age, and was higher in men than in women, and in urban than in rural residents. Prior stroke was associated with about twofold higher risk of Parkinson's disease (hazard ratio 1.94; 1.39–2.69). After adjustment for confounders in those without prior cardiovascular disease, a 5 kg/m2 higher body mass index was associated with 17% (1.17; 1.03–1.34: P = 0.019) higher risk of Parkinson's disease, but neither hypertension, diabetes, nor current cigarette smoking was significantly associated with Parkinson's disease. Interpretation Prior stroke and adiposity were each associated with higher risks of Parkinson's disease, but none of the other cardiovascular disease risk factors were significantly associated with Parkinson's disease in this population.